A Simple Step-by-Step Guide to Permanent Punctal Occlusion with the Ophthalmic Burr and Suture Technique - Gjukaj, Driton; Dacheva, Ivanka; Hildebrand, Göran Darius (Klinische Monatsblätter für Augenheilkunde, 2023)
The medical treatment of dry eye disease usually follows a step-wise approach to achieve clinical improvement, ranging from non-surgical interventions with intensive lubrication to permanent surgical punctal occlusion. While frequent lubrication is essential, the intense regime is often too burdensome and difficult to maintain at the required frequency. Punctal plugs are an invaluable alternative approach, but also have limitations, especially in conscious children, in whom inserting and re-inserting punctum plugs in clinic can be challenging. If a patient has permanent and severe dry eye disease and responded well to a trial of temporary punctal plugging, a permanent surgical solution should be considered next. Liu et al showed that a more successful, yet simple technique to achieve permanent occlusion is to combine de-epithelialising the punctum and ampulla with the immediate firm apposition of the de-epithelialised surface using a self-absorbable suture – with a success rate of 92% in a prospective study. This article demonstrates this technique step-by-step in an 8-year-old child with severe chronic dry eye disease following proton beam therapy for orbital rhabdomyosarcoma. She underwent this procedure with excellent results.
Keywords: ocular tumors; nasolacrimal ducts; pediatric ophthalmology; dry eye disease; punctal occlusion